2011
DOI: 10.1586/ern.11.19
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic bases for comorbidity of balance disorders, anxiety disorders and migraine: neurotherapeutic implications

Abstract: The comorbidity among balance disorders, anxiety disorders and migraine has been studied extensively from clinical and basic research perspectives. From a neurological perspective, the comorbid symptoms are viewed as the product of sensorimotor, interoceptive and cognitive adaptations that are produced by afferent interoceptive information processing, a vestibulo–parabrachial nucleus network, a cerebral cortical network (including the insula, orbitofrontal cortex, prefrontal cortex and anterior cingulate corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
139
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 164 publications
(240 reference statements)
3
139
0
5
Order By: Relevance
“…Defense mechanisms are also involuntary subconscious processes that are evoked in response to the perceived psychological risk and are used to reduce anxiety (28). Research has also shown that anxiety is very common among patients with migraine and such emotions are one of the most important factors causing migraine (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defense mechanisms are also involuntary subconscious processes that are evoked in response to the perceived psychological risk and are used to reduce anxiety (28). Research has also shown that anxiety is very common among patients with migraine and such emotions are one of the most important factors causing migraine (29).…”
Section: Discussionmentioning
confidence: 99%
“…Passive avoidance component indicates a lack of activity or surrender of a person to avoid punishing, and extinction component reflects stopping behaviors that are not rewarded in the aftermath (31). Heponiemi, T. (2004) also stated that the high sensitivity of behavioral inhibition system can make the patient prone to emotional distress in stressful situations and this emotional distress is one of the risk factors triggering reasons of migraines (29). Studies have also proved that people with migraine headaches have a stronger retention system compared to healthy people (2).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since a bidirectional correlation has been demonstrated between anxiety and vertigo, underlining possible common neural pathways, emotional factors may be hypothesized to play a role in a poorer postural control [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Частота сочетания мигрени с головокружением составляет 1-3% [5]. Первоначально мигрень и головокружение расценива-лись как коморбидные состояния, однако накопленный к настоящему времени клинический опыт позволяет сде-лать вывод о единых патогенетических механизмах этих нарушений [3][4][5].…”
unclassified
“…Нередко, примерно в 25% случаев, может возникать снижение уровня сознания. Затем в течение 60 минут присоединяется пульсирующая головная боль, чаще затылочная, но может быть и другой локализации [3][4][5].…”
unclassified